Frequency of Neutropenia in HIV Patients in Tertiary Care Hospital - Saliha Syed, Shahtaj Khan, Ansa Kulsoom Rehman, Sundas Iftikhar, Laila Bhadur, Hira Arooj (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: HIV is the systemic illness known as acquired immune deficiency syndrome (AIDS). According to the report of World Health Organization, 33.2 million people has infected by Human Immunodeficiency Virus. Objective: To determine the frequency of neutropenia in HIV patients in tertiary care hospital. Material and method: The current study was Descriptive, cross sectional study. It was carried out in Hematology department, Hayatabad Medical Complex, Peshawa from 30/10/2018 to 30/4/2019. The demographic and clinical data of all patients including age, gender, occupation, residence, neutrophil count and HIV status were recorded on predesigned proforma. The study data was analyzed using SPSS version 17. Results: In our study, totally 114 patients were included. There were 71(62%) male patients and 43(38%) female patients in our study. Based on neutropenia status 17(15%) patients were observed with neutropenia whereas 97(85%) patients were not observed with neutropenia Conclusion: Our study concludes that the frequency of neutropenia was 15% in HIV patients in tertiary care hospital. Keywords: neutropenia, HIV, AIDS, Prevalence